Avaliação dos efeitos do tratamento com LED em modelo experimental de síndrome do desconforto respiratório agudo - Costa, Silvia Goes (2016)
The acute respiratory distress syndrome (ARDS) is a severe lung disease, multifactorial, characterized by diffuse alveolar damage, infiltration of inflammatory cells, disruption of barrier of the alveolar epithelium, alveolar edema and impaired pulmonary gas exchange with high index of mortality and absence of efficient treatment and also, sepsis is the most common cause. The mechanisms involved in acute lung disease induced by systemic inflammation are investigated experimentally by administration of LPS systemically. This model develops inflammatory lesion with pulmonary neutrophilic infiltration and increased release of cytokines, including IL-1β and TNF- . The photobiomodulation has shown good results for various diseases with inflammatory character; however, there are few studies related with lung diseases. Considering that ARDS is an important pathology, we studied the effects of LED treatment on the development of ARDS. For this purpose, groups of mice were treated with LPS for ARDS induction and treated or not with LED (trachea and lungs) 2 and 6 h after the LPS injection. In parallel, non-manipulated group as well as treated only with LED were used as control. After 24h of LPS administration, we investigated the number of cells recruited in bronchoalveolar lavage (BAL), blood and bone marrow, quantification of cytokines in the BAL supernatant as well as evaluation of myeloperoxidase enzyme (MPO), oxidative burst, phagocytosis and histology. Our results indicated the beneficial effects of LED treatment on the ARDS model induced by LPS, since the treatment with LED significantly reduced the number of neutrophils recruited to the lung, MPO activity, oxidative burst, and also reduces the release of IL- 1β, IL-6 and TNF-α concomitantly with the increased levels of IFN-γ and IL-10 gene expression. Therefore, this study may provide important information to treatment of ARDS.